Performance characteristics of Indian hearing aids - SPS, Pandalay; SS, Murthy (Journal of All India Institute of Speech and Hearing, 1972)
Hearing aid is a miniaturised amplifier circuit, though it takes many forms, is designed specifically for improving human hearing. Reduction in size, improvement in acoustic quality and inconspicuousness to wear, than ever thought possible, have resulted, in greater acceptance of these hearing aids. Hearing Aids are made as glasses, as barrettes, for behind the ear use and for use directly on the ear, as well as in the form of conventional body hearing aid